Microfiber Pollution Environmental Challenges and Remediation Strategies - Sharma, Swati (Taylor & Francis Group, 2024)
Microfibers, synthetic fibers like polyester and nylon, are emerging contaminants widely distributed in air, water, and soil, posing significant ecological risks. The textile industry, driven by fast fashion trends, is a major source of microfiber pollution in both aquatic and terrestrial environments
Description based on publisher supplied metadata and other sources